Building Students' Sewing Equipment Competency In Technology Lessons (Texas Journal of Multidisciplinary Studies, 2024)
The article describes the issues of formation of students' technological competences in technology lessons, problems, development of competence formation methodology, factors that serve as a basis for determining the levels of formation of students' technological competences.